Mobilizing a CGIAR Agricultural Insurance Research Community - Garvin, S; Hansen, James (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
This report summarizes the proceedings of the workshop; “Mobilizing a CGIAR Agricultural Insurance Research Community,” held in Washington, D.C., January 20-22. 29 participants representing 14 CGIAR Centers (AfricaRice, CIAT, CIMMYT, ICARDA, ICRAF, IFPRI, ILRI, CCAFS, IWMI, IRRI) came together to participate in the workshop. The CCAFS Regional Programs of East and West Africa, and South and Southeast Asia were also represented. The workshop aimed to mobilize a community of practice on weather-related insurance for agricultural development and adaptation, take stock of relevant expertise and approaches across the CGIAR, and inform the development of funding proposals under CCAFS Flagship 2: Climate Information Services and Climate-Informed Safety Nets. Three opening keynote speakers provided background on index insurance and some of the successfully scaled projects, creating a context for the broader ideological discussions to follow. Some topics discussed included the use of index insurance as a development tool and as part of a greater risk management strategy; how agricultural research can engage the insurance industry; and index insurance data challenges. The second workshop day involved a mapping activity, to take stock of the activities of the CGIAR around the world in agricultural insurance as well as capture the methods, innovations, tools, and gaps and challenges of these projects. The third day supported workshop participants to explore synergies, and take advantage of writing a proposal for a funding opportunity through CCAFS. This workshop guided participants to share ideas, knowledge, approaches and resources, fostering a stronger community of practice across the CGIAR centers. Outputs from this workshop include a more populated community of practice website, several projects on index insurance approved for funding through CCAFS, and plans for a journal special issue.